THE APPLICATION OF LANGUAGE LEARNING STRATEGIES AND THEIR CORRELATION WITH STUDENTS’ ACHIEVEMENT (A STUDY ON TEN GRADES STUDENTS OF ACCELERATION CLASS, SENIOR HIGH SCHOOL 5, MALANG) - RACHMAWATI, DWITA LAKSMITA (Jurnal Ilmiah Mahasiswa FIB, 2013)
In Indonesia, especially in Malang, people begin to learn English in order to improve their English ability. Learning English is different from learning mother tongue. They have to learn words which are completely different in their spelling, pronunciation, and grammar. So, to make it easier, language learning strategies are needed. Thus, the researcher is interested to investigate the degree of the use of language learning strategies and to find out whether there are any correlation between six categories of language learning strategies used by the students of the first grade at acceleration class of SMA Negeri 5 Malang and their English achievement.This study used quantitative approach related to statistical analysis. The subjects being investigated were 60 students on ten grades at acceleration program, senior high school 5, Malang. The data were obtained from Strategy Inventory for Language Learning (SILL) questionnaire completed by the students and their school grade report of the first semester.            The result reveals that the use of overall language learning strategies falls into medium level. Specifically, the students prefer to use social strategies as the most frequently used, followed by memory, cognitive, affective, metacognitive and compensation strategies. A positive sufficient correlation is found between metacognitive strategies and English achievement. This sufficient correlation can be examined by looking at the context since English is used as the foreign language in Indonesia.            In sum, the students of the first grade at acceleration class are the moderate users of overall language learning strategies. Metacognitive strategies are found as the strategies that correlate with students’ achievement. Therefore, the teachers of acceleration class should introduce and promote more about the metacognitive strategies to their students in order to increase English achievement. The researcher also suggest for the readers, especially learners to apply metacognitive strategies because it can improve language skill.Keywords: language learning strategies, English proficiency, the Strategy Inventory for Language Learning (SILL) questionnaire, acceleration class.